Mechanisms of change in applied educational psychology - Gulliford, Anthea M. (2022)
Professional educational psychology has oriented itself to indirect service delivery for many decades, however the practice of this has been fragmented. Three strands of work presented here address a common overarching theme, namely, how educational psychology practitioners can optimise their work in support of learning environments: mechanisms of change. The first strand considers the relationship of the profession with an evidential basis for practice, with a focus on identification of mechanisms. Next, investigations of how tiered provision for social, emotional and mental health (SEMH) needs in schools can be optimised are offered. Finally, papers address the knowledge that educational psychologists can bring to optimising learning environments for children in schools. The work is informed by two guiding and parallel positions. The one, that of the scientist practitioner model, involving critical inquiry through diverse methods, to interrogate the evidential bases for professional practice, fuses with the other: an orientation that educational psychologists (EPs) must strive further to support the adults who work with children and young people, in indirect service delivery models.